A Studying on Ahmad Ar-Raisuni Thought: The Composision Of Sharia and Indonesian Political Fikh: STUDYING ON AHMAD AR-RAISUNI THOUGHT: THE COMPOSISION OF SHARIA AND INDONESIAN POLITICAL FIKH - Tutik Hamidah Hamidah; Irma Nur Hayati Hayati; Abbas Arfan Arfan (Fakultas Syariah Program studi Hukum Keluarga Islam IAI Al- Qodiri, 2022)
Abstract: Today, there are many politics issues in the classical-fikh literature which are not relevant in this time. This paper discusses the importance of a reconstruction and renewal of several issues in classical political fiqh that are adapted to the plural and heterogeneous Indonesian context. Therefore, the author combines the theory of Maqasid al-Syariah and the thought of Ahmad Ar-Raisuni which specifically raises political issues as the main of analytical sources. This article analyzed deeply with the qualitative method. The results of this rstudy are able to give birth to a new construction of Indonesian political fiqh which is formulated in four crucial issues, namely democracy, state format, criteria for leaders in Indonesia, and the application of Islamic sharia. Key Words: Ahmad-Raisuni, Sharia, Political Fikh